3R-HYDROXYMUSCARINE FROM L-RHAMNOSE WITHOUT PROTECTION - Mantell, S; Ford, P; Watkin, D; Fleet, G; Brown, D (1992)
The synthesis of the muscarine analogue 3R-3-hydroxymuscarine [(2S,3R,4R,5S)-3,4-dihydroxy-tetrahydro-N,N,N,5-tetramethyl-2-furanmethanimium tosylate] from L-rhamnose does not require the use of any protecting group. © 1992 Pergamon Press Ltd.